(untitled) (Journal of Global Accounting, 2025)
This study investigated the effects of dividend policy on the firm value of listed manufacturing companies in Nigeria. The population of the study consisted of 43 manufacturing companies listed on the Nigerian Exchange Group, and a sample of 20 companies was selected using judgmental sampling. The study covered a period of 15 years from 2009 to 2023 and employed the panel generalized method of moments regression to analyze the data. Tobin’s Q was used as a proxy for firm value, while dividend payout ratio, dividend yield, dividend per share, and earnings retention ratio were used as proxies for dividend policy. Firm size and liquidity were controlled for in the models. The results showed that dividend payout ratio and earnings retention ratio had a positive and significant effect on Tobin’s Q, while dividend yield had a negative and significant effect, and dividend per share had a positive but insignificant effect. Firm size and liquidity had significant and negative effects on firm value. Based on these findings, the study recommended that financial managers in Nigerian manufacturing firms should implement a balanced dividend payout policy, evaluate their dividend yield strategy to avoid compromising growth, identify an optimal dividend policy that aligns with investor preferences, and develop a flexible retention ratio that caters to changing investor demands. By adopting these strategies, managers could enhance firm value, satisfy investor expectations, and promote long-term sustainability. This study provided new evidence on the impact of dividend policy on firm value in the Nigerian manufacturing sector, offering valuable insights for managers, investors, and policymakers.